Dairy cow behaviour and physical activity as indicators of heat stress - L. M. C. Leliveld; D. Lovarelli; E. Riva; G. Provolo (Italian Journal of Animal Science)
Heat stress in dairy cattle is a major concern in modern dairy farming. Potentially, techniques developed in the field of precision livestock farming that monitor cow behaviour could enable an early detection of heat stress. However, for the definition of a behavioural response profile that is specific to heat stress, the identification of novel behavioural indicators of heat stress is still required. This study therefore studied the effect of hot weather conditions on known and novel behavioural parameters on 390 lactation dairy cows from three commercial dairy farms for 7.5 months, from late winter to early autumn. Cows were fitted with collars with accelerometer-based sensors to measure the Overall Dynamic Body Acceleration (ODBA) and six behaviour categories (lying idle, lying ruminating, standing idle, standing ruminating, eating, and other). Sensors in the barn measured temperature, humidity (to calculate the temperature-humidity index; THI), light, and wind speed. We found considerable variation across the three farms in the heat stress response, indicating the importance of studying heat stress across different farms to improve the applicability of the findings. Across the three farms, we found that an increase in THI led to an increase in the time spent standing, standing ruminating, and a decrease in the time spent eating, mean ODBA, and milk yield. This study identified new, sensitive, potential indicators of heat stress, like standing ruminating, which could be combined with established indicators, like eating, to improve the early detection and effective management of heat stress on diverse dairy cattle farms.